Nodular fasciitis in the mesentery, a differential diagnosis of peritoneal carcinomatosis - Shiga, Mai (World Journal of Gastroenterology, 2014)
Nodular fasciitis is a benign proliferative lesion composed of fibroblast-like cells that affects various sites in the body.We describe a patient with nodular fasciitis in the mesentery,encountered during laparotomy for the treatment of ascending colon cancer.The nodular fasciitis in our patient resembled peritoneal dissemination of malignancy on macroscopic observation.Because the treatment options change with concomitant peritoneal dissemination of gastrointestinal tract malignancy,recognition of this rare condition and preparation for unexpected nodular lesions are crucial.